Jaundice-predominant manifestation of Kawasaki disease in children - Ya-Ning Huang; Ya-Ning Huang; Chien-Yu Lin; Chien-Yu Lin; Chien-Yu Lin; Hsin Chi; Hsin Chi; Nan-Chang Chiu; Nan-Chang Chiu; Daniel Tsung-Ning Huang; Daniel Tsung-Ning Huang; Lung Chang; et al. (Frontiers Media S.A., 2024)
BackgroundA jaundice-predominant presentation of Kawasaki disease (KD) is atypical.MethodsA total of 12 children with KD with a predominant manifestation of jaundice at MacKay Children's Hospital were reviewed, along with 42 cases reported in the literature since 1990.ResultsThe median age of the 12 patients was 1.85 years (range: 3 months-4 years), and 66.6% were male. All of the patients had elevated liver function at presentation, 50% had hydrops of the gallbladder, and almost 60% had gastrointestinal symptoms and signs. Complete KD was evident in 11 of the 12 patients (91.7%), and two patients (16.7%) had recurrent episodes. All of the patients received intravenous immunoglobulin (IVIG); however, one-third were refractory to treatment. Corticosteroids were used in five (41.7%) of the patients. Three (25%) of the patients had shock, and seven (58.3%) had coronary artery abnormalities, of whom one (8.3%) had persistent coronary artery aneurysm and the others recovered. A review of the 42 cases in the literature showed that the children with a jaundice-predominant presentation of KD had high rates of IVIG-refractory disease (25%), coronary artery abnormalities (25%), shock (13.2%), and corticosteroid treatment (24.2%).ConclusionsChildren with KD presenting with a jaundice-predominant manifestation are at a higher risk of IVIG-refractory disease, coronary artery abnormalities, and more recurrent episodes. Physicians should be aware of the risk of shock in this population.